Assessing digital self-efficacy: Review and scale development. (December 2022) - Ulfert-Blank, Anna-Sophie; Schmidt, Isabelle
Abstract: Today, digitalization is affecting all areas of life, such as education or work. The competent use of digital systems (esp. information and communication technologies [ICT]) has thus become an essential skill. Despite longstanding research on human-technology interaction and diverse theoretical approaches describing competences for interacting with digital systems, research still offers mixed results regarding the structure of digital competences. Self-efficacy is described as one of the most critical determinants of competent digital system use, and various self-report scales for assessing digital self-efficacy have been suggested. Yet, these scales largely differ in their proposed specificity, structure, validation, and timeliness. The present study aims at providing a systematic overview and comparison of existing measures of digital self-efficacy (DSE) to current theoretical digital competence frameworks. Further, we present a newly developed scale that assesses digital self-efficacy in heterogeneous adult populations, theoretically founded in the DigComp 2.1 and social-cognition theory. The factorial structure of the DSE scale is assessed to investigate multidimensionality. Further, the scale is validated considering the nomological network (actual ICT use, technophobia). Implications for research and practice are discussed. Highlights: Scoping review of scales that assess digital/ICT related self-efficacy. Scale development of an economical scale assessing multifaceted digital self-efficacy (DSE). Validation of the DSE scale in heterogeneous German adult population. Measurement invariance testing across gender of the DSE scale. Discussion of existing and DSE scale regarding application fields.